Efforts to Optimize the Management of Regional Wealth in an Effort to Increase Regional Original Income - Lubis, Ahmad Yasir; Eddy, Triono; Wajdi, Farid (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The condition of BUMN is one step ahead compared to the business activities carried out by BUMD. Another problem lies in the Human Resources (HR) and management of BUMD management. The relatively small share of the Regional Company's profit as one of the sources of regional PAD is that most of its businesses are relatively medium and small scale, in addition to many of which have not been organized based on the principles of the company's economy, but are relatively more based on considerations of public serviceIn a limited liability company, shares owned by an individual or legal entity provide rights in the form of dividends to him as regulated in Article 52 paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies. In order to realize these conditions, ideally the construction of BUMD is directed to be in the form of a corporation. In order to manage BUMD in the form of a corporation, it can adopt the concept of managing state-owned companies under the auspices of the Ministry of BUMN which has implemented Good Corporate Governance in its management. In order to realize Good Corporate Governance in BUMD, a good governance structure is needed. Governance Structure or termed governance structure can be interpreted as a framework in an organization to apply various principles so that these principles can be shared, implemented and controlled. Specifically, the governance structure must be designed to support the running of organizational activities in a responsible and controlled manner